ω-3PUFA supplementation ameliorates adipose tissue inflammation and insulin-stimulated glucose disposal in subjects with obesity: a potential role for apolipoprotein E - Hernandez, James D.; Li, Ting; Rau, Cassandra M.; LeSuer, William E.; Wang, Panwen; Coletta, Dawn K.; Madura, James A.; Jacobsen, Elizabeth A.; De Filippis, Eleanna (International Journal of Obesity, 2021)
Background Long chain omega-3 polyunsaturated fatty acids (ω-3PUFA) supplementation in animal models of diet-induced obesity has consistently shown to improve insulin sensitivity. The same is not always reported in human studies with insulin resistant (IR) subjects with obesity. Objective We studied whether high-dose ω-3PUFA supplementation for 3 months improves insulin sensitivity and adipose tissue (AT) inflammation in IR subjects with obesity. Methods Thirteen subjects (BMI = 39.3 ± 1.6 kg/m 2 ) underwent 80 mU/m 2 ·min euglycemic-hyperinsulinemic clamp with subcutaneous (Sc) AT biopsy before and after 3 months of ω-3PUFA (DHA and EPA, 4 g/daily) supplementation. Cytoadipokine plasma profiles were assessed before and after ω-3PUFA. AT-specific inflammatory gene expression was evaluated on Sc fat biopsies. Microarray analysis was performed on the fat biopsies collected during the program. Results Palmitic and stearic acid plasma levels were significantly reduced ( P < 0.05) after ω-3PUFA. Gene expression of pro-inflammatory markers and adipokines were improved after ω-3PUFA ( P < 0.05). Systemic inflammation was decreased after ω-3PUFA, as shown by cytokine assessment ( P < 0.05). These changes were associated with a 25% increase in insulin-stimulated glucose disposal (4.7 ± 0.6 mg/kg ffm•min vs. 5.9 ± 0.9 mg/kg ffm•min) despite no change in body weight. Microarray analysis identified 53 probe sets significantly altered post- ω-3PUFA, with Apolipoprotein E (APOE) being one of the most upregulated genes. Conclusion High dose of long chain ω-3PUFA supplementation modulates significant changes in plasma fatty acid profile, AT, and systemic inflammation. These findings are associated with significant improvement of insulin-stimulated glucose disposal. Unbiased microarray analysis of Sc fat biopsy identified APOE as among the most differentially regulated gene after ω-3PUFA supplementation. We speculate that ω-3PUFA increases macrophage-derived APOE mRNA levels with anti-inflammatory properties.